Characterization of typhoid intestinal perforation in Africa: results from the severe typhoid fever surveillance in Africa program - Birkhold, Megan; Datta, Shrimati; Pak, Gi Deok; Im, Justin; Ogundoyin, Olakayode O; Olulana, Dare I; Lawal, Taiwo A; Afuwape, Oludolapo O; Kehinde, Aderemi; Phoba, Marie-France; Nkoji, Gaëlle; Aseffa, Abraham; et al. (Open Forum Infectious Diseases, 2023)
Typhoid intestinal perforation (TIP) remains the most serious complication of typhoid fever. In many countries, the diagnosis of TIP relies on intraoperative identification, as blood culture and pathology capacity remain limited. As a result, many cases of TIP may not be reported as typhoid. This study demonstrates the burden of TIP in sites in Burkina Faso, Democratic Republic of Congo (DRC), Ethiopia, Ghana, Madagascar, and Nigeria.Patients with clinical suspicion of nontraumatic intestinal perforation were enrolled and demographic details, clinical findings, surgical records, blood cultures, tissue biopsies, and peritoneal fluid were collected. Participants were then classified as having confirmed TIP, probable TIP, possible TIP, or clinical intestinal perforation based on surgical descriptions and cultures.A total of 608 participants were investigated for nontraumatic intestinal perforation; 214 (35%) participants had surgically-confirmed TIP and 33 participants (5%) had culture-confirmed typhoid. The overall proportion of blood or surgical site Salmonella enterica subspecies enterica serovar Typhi positivity in surgically verified TIP cases was 10.3%. TIP was high in children aged 5-14 years in DRC, Ghana, and Nigeria. We provide evidence for correlation between monthly case counts of S. Typhi and the occurrence of intestinal perforation.Low S. Typhi culture positivity rates, as well as a lack of blood and tissue culture capability in many regions where typhoid remains endemic, significantly underestimate the true burden of typhoid fever. The occurrence of TIP may indicate underlying typhoid burden, particularly in countries with limited culture capability.